EFFECT OF WORK SATISFACTION AND ORGANIZATIONAL CULTURE ON COMMITMENT TO LECTURER PROFESSION IN BATAM UNIVERSITY – INDONESIA - Widia, Elli; Wibisono, Chablullah (International Journal of Psychosocial Rehabilitation, 2020)
: Professional commitment is a form of work commitment that impacts individual work behavior that is seen in productivity and performance. This study aims to reveal the effect of job satisfaction and organizational culture on the commitment to the teaching profession. The study was conducted at Batam University. This research method uses a survey method with a path analysis approach. The results of this study found that: (1) the direct effect of job satisfaction on the commitment to the teaching profession is shown through the price of the path coefficient py1 = 0.617 with tcount> table. This confirms that job satisfaction has a direct positive effect on the commitment to the teaching profession; (2) the direct influence of organizational culture on the commitment to the teaching profession has a path coefficient value of py2 = 0.281 with tcount> table. This finding confirms that organizational culture has a direct positive effect on the commitment to the teaching profession. Thus, it can be said that job satisfaction and organizational culture have a direct positive effect on the commitment to the teaching profession at the University of Batam. Based on the above research findings, it can be concluded that job satisfaction and organizational culture are variants of commitment to the teaching profession. Thus, efforts to increase commitment to the teaching profession can be made by increasing job satisfaction and organizational culture. Thus, it can be said that job satisfaction and organizational culture have a direct positive effect on the commitment to the teaching profession at the University of Batam. Based on the above research findings, it can be concluded that job satisfaction and organizational culture are variants of commitment to the teaching profession. Thus, efforts to increase commitment to the teaching profession can be made by increasing job satisfaction and organizational culture. Thus, it can be said that job satisfaction and organizational culture have a direct positive effect on the commitment to the teaching profession at the University of Batam. Based on the above research findings, it can be concluded that job satisfaction and organizational culture are variants of commitment to the teaching profession. Thus, efforts to increase commitment to the teaching profession can be made by increasing job satisfaction and organizational culture.